Systematic Analysis of Hsf Family Genes in the Brassica napus Genome Reveals Novel Responses to Heat, Drought and High CO2 Stresses - Zhu, Xiaoyi; Huang, Chunqian; Zhang, Liang; Liu, Hongfang; Yu, Jinhui; Hu, Zhiyong; Hua, Wei (Frontiers in Plant Science, 2017)
Drought and heat stress are major causes of lost plant crop yield. In the future, high levels of CO2, in combination of other abiotic stress factors, will become a novel source of stress. Little is known of the mechanisms involved in the acclimation responses of plants to this combination of abiotic stress factors, though it has been demonstrated that heat shock transcription factors (Hsfs) are involved in plant response to various abiotic stresses. In this study, we performed a genome-wide identification and a systematic analysis of genes in the Hsf gene family in Brassica napus. A total of 64 genes encoding Hsf proteins were identified and classified into 3 major classes: A, B and C. We found that, unlike in other eudicots, the A9 subclass is absent in rapeseed. Further gene structure analysis revealed a loss of the only intron in the DBD domain for BnaHsf63 and -64 within class C, which is evolutionarily conserved in all Hsf genes. Transcription profile results demonstrated that most BnaHsf family genes are upregulated by both drought and heat conditions, while some are responded to a high CO2 treatment. According to the combined RNA-seq and qRT-PCR analysis, the A1E/A4A/A7 subclasses were upregulated by both drought and heat treatments. Members in class C seemed to be predominantly induced only by drought. Among BnaHsf genes, the A2/A3/B2 subclasses were regulated by all three abiotic stresses. Members in A2/B2 subclasses were upregulated by drought and heat treatments, but were downregulated under high CO2 conditions. While the A3 subclass was upregulated by all the three abiotic stresses. Various stress-related cis-acting elements, enriched in promoter regions, were correlated with the transcriptional response of BnaHsfs to these abiotic stresses. Further study of these novel groups of multifunctional BnaHsf genes will improve our understanding of plant acclimation response to abiotic stresses, and may be useful for improving the abiotic stress resistance of crop varieties.